Gli studi comparativi in educazione. Una introduzione storico-critica - Donatella Palomba (LED Edizioni Universitarie, 2011)
Comparative Studies in Education. An Historical-Critical Introductions Comparative studies in education constitute a rather complex research field. It is not unusual to hear calls for their redefinition, starting from the consideration that the dynamics of globalisation seem to question some characterising elements like the very unit of comparison adopted, often identified with the State. The author aims to show how this conception is an oversimplification in that a serious consideration of comparative studies and theories demonstrates how, as a unit, the State has actually not been the exclusive object of study at all, historically speaking. Instead, while bearing in mind the limitations of studies exclusively based on the State, the simplistic assumption of going beyond the State must at least be justified in some way. Without careful attention to individual contexts and an in-depth analysis of their peculiarities, any «comparison» remains vacuous or, rather, cannot be defined as real comparison, and both the theoretical end and the melioristic one are ineluctably destined not to be achieved. Over and beyond the specificities linked to individual research approaches, this remains a fundamental call for method which, ultimately, is linked to what Sadler recommended over a century ago.